Wpływ Liniowo-Sprężystego Odciążenia na Dynamikę Obiektu Umieszczonego w Sprężysto-Plastycznym Gruncie - Łęgowski, Z.; Włodarczyk, E. (Engineering Transactions, 1973)
The paper presents an analytical solution of the problem of interaction of an elastic-plastic stress wave with a plane wall resting on a linearly-elastic halfspace and covered by a soil layer of thickness h. The soil is approximated by a model with linear loading and linearly elastic unloading branches. Influence of the linearly elastic unloading within the layer upon the parameters of motion of the wall is examined in detail, what makes it possible to establish the conditions under which the simplified model with rigid unloading may be used.